Bibliometric Analysis: Trends Research on Local Wisdom in Science Learning and Its Implications for Strengthening Love Local Culture - Dwi Agnes Setianingrum; Jumadi Jumadi; Suyanta Suyanta; Sabar Nurohman; Sri Rejeki Dwi Astuti; Iffah Nurlathifah Fikri (Pascasarjana, Mataram University, 2023)
Much research has been carried out on local wisdom at the junior high school level nationally, but research that has been published internationally and is Scopus indexed specifically discusses local wisdom at the junior high school level is still very minimal. The purpose of writing this research is as material to find out trends in local wisdom research in junior high school science learning. This study uses a bibliometric analysis method that uses sources from Scopus with publication limits from 2019 to 2023 on the Scopus database, and utilizes the VOSviewer application as a visualization tool. Data analysis through the Scopus database in this research was based on search results with local wisdom keywords written in the title words column and science learning as keywords. Found 45 publications in Scopus during 2019-2023 that discuss local wisdom in junior high schools. Published articles about local wisdom in junior high school science learning during 2019-2023 will be more researched in 2020 based on the results of data analysis through the Scopus database. The results of the bibliometric analysis research show that the trend of research on local wisdom at the junior high school level in the five year period (2019-2023) has focused more on the position of students as learning subjects and the development of research on local wisdom in junior high schools that specifically discusses the implications for strengthening the attitude of love for local culture for students have not been studied much